Uncomplicated falciparum malaria among schoolchildren in Bajil district of Hodeidah governorate, west of Yemen: association with anaemia and underweight - Talal S. Alwajeeh; Rashad Abdul-Ghani; Amal F. Allam; Hoda F. Farag; Safia S. M. Khalil; Amel Y. Shehab; Mona H. El-Sayad; Raed A. Alharbi; Shaia S. R. Almalki; Ahmed A. Azazy (Malaria Journal, 2020)
Abstract Background Malaria, malnutrition and anaemia are major public health problems in Yemen, with Hodeidah being the most malaria-afflicted governorate. To address the lack of relevant studies, this study was conducted to determine the prevalence of Plasmodium falciparum and its relation to nutritional status and haematological indices among schoolchildren in Bajil district of Hodeidah governorate, west of Yemen. Methods A cross-sectional study was conducted among 400 schoolchildren selected randomly from four schools in Bajil district. Data about demographic characteristics, risk factors and anthropometric measurements of age, height and weight were collected. Duplicate thick and thin blood films were prepared, stained with Giemsa and examined microscopically for malaria parasites. The density of P. falciparum asexual stages was estimated on thick films. EDTA-blood samples were examined for the haematological indices of haemoglobin (Hb) and blood cell counts. Results Plasmodium falciparum was prevalent among 8.0% (32/400) of schoolchildren with a mean parasite density of 244.3 ± 299.3/µL of blood and most infections showing low-level parasitaemia, whereas Plasmodium vivax was detected in one child (0.25%). Residing near water collections was a significant independent predictor of falciparum malaria [adjusted odds ratio (AOR) = 2.6, 95.0% CI 1.20–5.72; p = 0.016] in schoolchildren. Mild anaemia was prevalent among more than half of P. falciparum-infected schoolchildren and significantly associated with falciparum malaria (AOR = 5.8, 95.0% CI 2.39–14.17; p < 0.001), with a mean Hb concentration of 10.7 ± 1.0 g/dL. Although the mean values of the total white blood cells, monocytes and platelets were significantly lower in infected than non-infected schoolchildren, they were within normal ranges. More than half of the children were malnourished, with stunting (39.3%) and underweight (36.0%) being the most prevalent forms of malnutrition; 6.3% of children were wasted. Underweight (AOR = 5.3, 95.0% CI 2.09–13.62; p < 0.001) but not stunting or wasting, was a significant predictor of falciparum malaria among schoolchildren. Conclusion Asymptomatic falciparum malaria is prevalent among schoolchildren in Bajil district of Hodeidah Governorate, with predominance of low parasitaemic infections and significant association with mild anaemia and underweight. Residence near water collection is a significant predictor of infection with falciparum malaria among schoolchildren. Further studies among children with severe malaria and those with high parasite densities are recommended.